2023
DOI: 10.3390/audiolres13010006
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Relevance of Hearing Dogs from the Owner’s Perspective: An Explorative Study among Adults with Hearing Loss

Abstract: This study aimed to explore perceptions and experiences about how owning a hearing dog can influence the functioning and the autonomy of people with hearing loss. Three adults participated in a semi-structured interview. The interviews were video recorded, transcribed, and coded. A procedure combining qualitative content analysis and interpretative phenomenological analysis was used. The study shows how specific aspects of hearing dogs are associated with increased autonomy and sense of security among owners. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Experiences of social stigma and social acceptance appear to vary based on the type of service dog interventions. For example, social acceptance and recognition are among the most common benefits reported by individuals with hearing dogs ( 41 ), but stigma and judgement are among the biggest negatives reported by veterans with service dogs for PTSD ( 37 , 42 ). Although no participants in our study experienced this as a negative, one study has previously identified that the experience of increased public visibility may be unwanted for some caretakers ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Experiences of social stigma and social acceptance appear to vary based on the type of service dog interventions. For example, social acceptance and recognition are among the most common benefits reported by individuals with hearing dogs ( 41 ), but stigma and judgement are among the biggest negatives reported by veterans with service dogs for PTSD ( 37 , 42 ). Although no participants in our study experienced this as a negative, one study has previously identified that the experience of increased public visibility may be unwanted for some caretakers ( 20 ).…”
Section: Discussionmentioning
confidence: 99%